Efficacy, acceptability and safety of Internet‐delivered psychological therapies for fibromyalgia syndrome: A systematic review and meta‐analysis of randomized controlled trials. (6th August 2018) - Bernardy, K.; Klose, P.; Welsch, P.; Häuser, W.
Abstract: This systematic review aimed at evaluating the efficacy, acceptability and safety of Internet‐based psychological therapies (IPTs) in fibromyalgia syndrome (FMS). Clinicaltrials.gov, Cochrane Library, MEDLINE, PsycINFO and SCOPUS were searched from inception to January 2018. Randomized controlled trials (RCTs) comparing IPTs with controls were analysed. Primary outcomes were ≥50% pain relief, disability, negative mood, acceptability and safety at end of therapy and at 6‐month follow up. Effects were summarized by a random effects model using risk differences (RD) or standardized mean differences (SMD) with 95% confidence intervals (CI). Six RCTs using different types of Internet‐based cognitive‐behavioural therapies [ICBTs] (acceptance‐based; exposure‐based; traditional) with 493 patients were included. At the end of treatment, ICBTs were superior to controls (waiting list, attention control, treatment as usual) in reducing negative mood (SMD −0.51 [95% CI −0.87 to −0.15]) (moderate quality evidence) and disability (SMD −0.56 [95% CI −1.00 to −0.13]) (moderate quality evidence). There were no statistically significant differences between ICBTs and controls in pain relief of 50% or greater (RD 0.09 [95% CI −0.02 to 0.20] (moderate quality evidence) and acceptability (moderate quality evidence). No data on safety and any outcomes at long‐term follow‐up compared to controls were found. The data available did not allow statistical comparisons between unguided and guided ICBTs and of ICBTs versus traditional face‐to‐face therapies. ICBTs provided a clinically relevant benefit over control interventions in reducing negative mood and disability at the end of treatment. Significance: Internet‐delivered cognitive behavioural therapies provided a clinically relevant benefit in reducing negative mood and disability in patients with FMS at the end of treatment if compared to waiting list, treatment as usual and attention controls.